The saliency of the CEO pay ratio - Boone, Audra; Starkweather, Austin; White, Joshua T (Review of Finance, 2024)
Abstract The US Securities and Exchange Commission’s mandated CEO pay ratio is a simple, but salient, metric that could resonate with employees given it focuses on their compensation. Reporting a relatively or surprisingly high ratio reduces employee perceptions of their pay, views of the CEO, and hampers productivity growth. Employee pay satisfaction drops after disclosing a high ratio even if their wages were previously disclosed and when the pay ratio disclosure adds little new information. Disclosures by firms with a high ratio contain more discretionary language to explain the ratio or portray employee relations positively and are more likely to be covered by the media. However, neither information source substantially alters the employee response to a salient ratio. Our work illustrates that requiring firms to disclose a salient metric can have unintended consequences on employees and suggests caution in requiring firms to report simplified Environmental, Social, and Governance (ESG) metrics that are inherently multifaceted.